A comparative quality assessment of evidence‐based clinical guidelines in endocrinology. (7th January 2013) - Hazlehurst, Jonathan M.; Armstrong, Matthew J.; Sherlock, Mark; Rowe, Ian A.; O'Reilly, Michael W.; Franklyn, Jayne A.; Stewart, Paul M.; Tomlinson, Jeremy W.
Summary Context Evidence‐based clinical guidelines in endocrinology attempt to improve and standardize patient care. There has been an expansion in guideline production although some of the heterogeneous methods used to assess the quality of the underlying evidence base might limit interpretation and implementation. Design Current and archived guidelines from major endocrine organizations were accessed. The organizations used six different methods to rate underlying evidence, including Grading of Recommendations Assessment, Development and Evaluation (GRADE). To allow direct comparison between guidelines produced by different organizations, the levels of evidence used to generate them were graded according to the standardized system: 'high' based on randomized, controlled trials and meta‐analyses, 'moderate' based on nonrandomized studies and 'low' based on expert opinion. Results There was an increase in guideline production over time (1995–2000 = 9, 2001–2005 = 12, 2006–2011 = 36). Three guidelines were updated with an average delay of 4·3 years and an increase in recommendations per guideline (21·1%). Encouragingly, whilst updates had similar levels of 'high'‐quality evidence, there was increased reliance on 'moderate'‐category evidence and less on 'low''‐quality evidence' ('high', 6·3% vs 6·5%; 'moderate', 46·1% vs 59·1%; 'low', 47·7% vs 34·4%). A high proportion of 'low'‐category evidence was seen throughout all organizations. Rarer conditions and recommendations concerning treatment efficacy were particularly reliant on 'low'‐category evidence. Conclusions The level of evidence underpinning current guidelines highlights areas in need of well‐designed, collaborative clinical research. Furthermore, criteria to define when guideline updates are necessary are currently lacking. A standardized method of assessment, such as GRADE, would promote understanding and compliance by guideline users with the ultimate aim of enhancing patient care.